Manifestation of linguistic aesthetics and characters in Javanese wedding ceremonial discourse - Mulyana Mulyana (Indonesian Journal of Applied Linguistics, 2023)
This research is an exploration into a wedding ceremonial discourse (WCD) in the contexts of Javanese traditional ceremonies. In doing so, the study focuses the observation in the practices in Yogyakarta and the surrounding regions, where Javanese traditional wedding is still a norm. The data were collected in two main sources, namely the spoken discourses from the speech makers in wedding ceremonies, and written references on wedding scripts used as supplementary data. Two main features are shown as a result of the study. First, Javanese language aesthetics are manifested in the expressions of delivered by the speech makers in the wedding ceremonies, despite the use of occasionalÂ  mix with Indonesian. Secondly, the use of the language in WCD also reflect the expected characters of the speech makers in the ceremonies. WCD shows dynamics of language use. Within its development, the discourse of wedding speech in the Javanese language will continue to sustain and develop under several changes with regards to the ceremonial procedures, sentence structure, diction, and language selection.